Association between Oral Parafunctional Habits with Personality Type in Individuals - Hira Butt, Nauman Rauf Khan, Saeed ur Rehman, Zainab Waheed, Darab Fatima Babary, Taimur Hassan Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the association between oral parafunctional habits and personality traits in individuals. Methodology: A Cross-sectional descriptive study was conducted at the College of Dentistry, Sharif Medical and Dental College, Lahore, over 5 months, from July to November 2021. All individuals, irrespective of their age and gender and those who reported having oral parafunctional habits, were included. Individuals with a history of smoking and those with any systemic illness were excluded. Data was collected using a medical questionnaire and a ten-item personality inventory scale (TIPI). Results: The association between personality traits and oral parafunctional habits was not statistically significant. The association between extraversion personality trait and nail-biting (p=0.267), teeth grinding (p=00754), teeth clenching (p=0.450) and biting hard objects (p=0.582) was not significant. The association between agreeableness and nail-biting (p=0.112), teeth grinding (p=0.612), teeth clenching (p=0.430), biting hard objects (p=0.639) and chewing gum (p=1.000) was not significant. The association between conscientiousness and nail-biting (p=0.588), teeth grinding (p=0.588), teeth clenching (p=0.325), biting hard objects(p=1.000) and chewing gum (p=1.000) was non-significant. Similarly, the association between personality traits of emotional stability and openness to experience with nail-biting (p=0.138, p=0.594 respectively), Teeth grinding (p=0.586,0.594 respectively), teeth clenching (p=0.813, p=1.000 respectively), biting hard objects (p=0.075, p= 0.347 respectively) and chewing gum (p=0.585, p=0.556 respectively) was non-significant. Conclusion: The majority of individuals from all personality types had a habit of teeth clenching followed by biting on hard objects. The least prevalent parafunctional habit reported by them was the parafunctional habit of chewing gum.